Transformasi budaya dalam era digital: tantangan dan peluang - Fitriadi, I'tibar - (Maliki Interdisciplinary Journal, 2025)
The digital era has brought significant changes to many aspects of societal life, from communication methods, interaction patterns, to the discussion of trends among youth groups, which are dynamic and rapidly evolving. Digitalization also impacts the cultural values found in society, presenting major challenges related to the shifting of traditional values that have long been upheld. On the other hand, digitalization opens up tremendous opportunities to preserve and even strengthen local culture through the use of technological innovations, such as social media, digital platforms, and culture-based applications, making it easier for society to access and promote local culture to the international arena. Digitalization allows local culture to spread more widely and gain appreciation from many circles. This article aims to analyze the impact of cultural transformation resulting from digitalization, identify emerging challenges, and explore opportunities that can be utilized to maintain the relevance of local culture amidst the intensifying global flow. Through this approach, it is hoped that various strategies can be discovered to optimize the role of culture as an essential element in shaping the national identity in this challenging digital era. It is important for society to use technology wisely to maintain a balance between preserving local values and adapting to the development of the times.